2013
DOI: 10.1021/ci300625c
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore and 3D-QSAR Characterization of 6-Arylquinazolin-4-amines as Cdc2-like Kinase 4 (Clk4) and Dual Specificity Tyrosine-phosphorylation-regulated Kinase 1A (Dyrk1A) Inhibitors

Abstract: Cdc2-like kinase 4 (Clk4) and dual specificity tyrosine-phosphorylation-regulated kinase 1A (Dyrk1A) are protein kinases that are promising targets for treatment of diseases caused by abnormal gene splicing. 6-Arylquinazolin-4-amines have been recently identified as potent Clk4 and Dyrk1A inhibitors. In order to understand the structure–activity correlation of these analogs, we have applied ligand-based pharmacophore and 3D-QSAR modeling combined with structure-based homology modeling and docking. The high R2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Some of these results are in agreement with those presented by Pan et al [ 34 ] in an atom-based 3D-QSAR modeling study, using this same series of 6-arylquinazolin-4-amines. They observed that the inhibitory activity increases when R 1 is a phenyl ring substituted with a hydrophilic and electron-withdrawing group, R 3 is a heterocyclic ring substituted with a hydrophobic group, and the nitrogen atom of the amine group is substituted with a bulky hydrophobic group.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Some of these results are in agreement with those presented by Pan et al [ 34 ] in an atom-based 3D-QSAR modeling study, using this same series of 6-arylquinazolin-4-amines. They observed that the inhibitory activity increases when R 1 is a phenyl ring substituted with a hydrophilic and electron-withdrawing group, R 3 is a heterocyclic ring substituted with a hydrophobic group, and the nitrogen atom of the amine group is substituted with a bulky hydrophobic group.…”
Section: Resultssupporting
confidence: 91%
“…They observed that the inhibitory activity increases when R 1 is a phenyl ring substituted with a hydrophilic and electron-withdrawing group, R 3 is a heterocyclic ring substituted with a hydrophobic group, and the nitrogen atom of the amine group is substituted with a bulky hydrophobic group. On the other hand, the inhibitory activity decreases when R 2 is a hydrogen atom and R 1 /R 3 are hydrophobic groups [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The correct pharmacophore model gives the information regarding hydrogen binding properties (acceptor or donor), hydrophobic properties, and aromatic functionality presented by compounds in the dataset. This information could be exploited for the characterization of structurally diverse compounds acting on the same bio-molecules [16].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it cannot reflect the quantitative structure-activity relationship (QSAR) as it just considers a single target or a single target-ligand complex [ 17 ]. Compared with structure-based model, ligand-based pharmacophore is more frequently used, which extracts common chemical features from aligned compound structures interacting with the same target, based on the hypothesis that compounds interacting with the same protein target may share similar chemical structure and physicochemical properties [ 18 , 19 ]. The pivotal issues of the ligand-based model are the modeling of ligand flexibility, the alignment methods of molecules and the selection of training set.…”
Section: Introductionmentioning
confidence: 99%